Analisis Kesulitan Membaca Pemahaman pada Siswa Sekolah Dasar - Agnesya, Aira Mahgi; Wiarsih, Cicih (Universitas Sebelas Maret, 2025)
Reading comprehension difficulties among elementary school students remain a common issue, yet they have not been extensively studied, despite their significant impact on students academic performance and literacy skills. This study aims to describe the factors contributing to students' difficulties in understanding reading materials and to identify the strategies employed by teachers, parents, and schools to address these challenges. A qualitative approach with a case study design was used, involving 11 fifth-grade students from fifth grade C at SD Negeri Ledug, selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that reading comprehension difficulties stem from internal factors, such as low reading interest, weak memory, and limited vocabulary; as well as external factors, including limited instructional time, lack of parental support, an unconducive learning environment, and the influence of digital devices. The strategies implemented to overcome these issues include learning assistance from teachers and parents, and the implementation of school-based literacy programs. The study concludes that a synergistic collaboration between teachers, parents, and schools is essential in enhancing students' reading comprehension skills. Kesulitan membaca pemahaman pada siswa sekolah dasar masih sering terjadi, namun belum banyak dikaji secara mendalam, padahal hal ini memengaruhi prestasi akademik dan kemampuan literasi. Penelitian ini bertujuan untuk mendeskripsikan faktor penyebab kesulitan memahami isi bacaan dan strategi yang diterapkan oleh guru, orang tua, dan sekolah. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan 11 siswa kelas VC SD Negeri Ledug yang dipilih melalui teknik purposive sampling. Data diperoleh melalui observasi, wawancara, dan dokumentasi, serta dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa kesulitan membaca pemahaman disebabkan oleh faktor internal, seperti rendahnya minat baca, lemahnya daya ingat, dan keterbatasan kosakata; serta faktor eksternal seperti waktu pembelajaran yang terbatas, kurangnya dukungan orang tua, lingkungan belajar tidak kondusif, dan pengaruh gawai. Strategi yang dilakukan meliputi pendampingan belajar oleh guru dan orang tua, serta pengadaan program literasi sekolah. Penelitian ini menyimpulkan pentingnya sinergi antara guru, orang tua, dan sekolah dalam meningkatkan keterampilan membaca pemahaman siswa.